2014
DOI: 10.1517/14728222.2014.957671
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a subset of patients with acute myeloid leukemia characterized by long-termin vitroproliferation and altered cell cycle regulation of the leukemic cells

Abstract: We identified a subset of AML patients characterized by long-term in vitro cell proliferation and altered expression of cell cycle regulators that may be potential candidates for treatment of AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 72 publications
2
21
0
Order By: Relevance
“…In agreement with previous results [13], the capacity of long-term AML cell proliferation in the absence of supportive cells was not associated with the differentiation status of the primary AML cells at the time of diagnosis, i.e., cultures with and without this capacity did not differ with regard to morphological signs of differentiation (FAB classification) or expression of the CD34 stem cell marker. Furthermore, apart from cell number colony formation after long-term culture appeared to be independent of common prognostic factors such as patient age, hemoglobin levels, peripheral blood blast count, cytogenetics, NPM1 mutations, and secondary or relapsed versus de novo AML (an overview of patient details is provided in Supplementary Table S1).…”
Section: Resultssupporting
confidence: 92%
“…In agreement with previous results [13], the capacity of long-term AML cell proliferation in the absence of supportive cells was not associated with the differentiation status of the primary AML cells at the time of diagnosis, i.e., cultures with and without this capacity did not differ with regard to morphological signs of differentiation (FAB classification) or expression of the CD34 stem cell marker. Furthermore, apart from cell number colony formation after long-term culture appeared to be independent of common prognostic factors such as patient age, hemoglobin levels, peripheral blood blast count, cytogenetics, NPM1 mutations, and secondary or relapsed versus de novo AML (an overview of patient details is provided in Supplementary Table S1).…”
Section: Resultssupporting
confidence: 92%
“…In cytological experiments, the knockdown of DLGAP5 caused inhibition of proliferation, migration and invasion of NSCLC cells (10). Previous studies have also shown that the expression levels of DLGAP5 are upregulated in bladder (11), prostate (12) and liver cancer (13), as well as leukemia (14) were associated with poor prognosis. In the present study, DLGAP5 was identified to be a hub gene in GEO and Gene Expression-Based Outcome for BC Online (GOBO) databases.…”
Section: Introductionmentioning
confidence: 91%
“…The downregulation of CCNF was also established in B-cell ALL (42). NUSAP1 and CCNF were associated with altered cell cycle in acute myeloid leukemia (43), therefore providing further evidence of the role of the two genes in cell cycle modulation. These results collectively suggest that the 3 genes ( MKI67 , NUSAP1 and CCNF ) mediate cell cycle processes and may have regulatory roles in the B-cell ALL progression.…”
Section: Discussionmentioning
confidence: 91%